2013
DOI: 10.1074/jbc.r113.479519
|View full text |Cite
|
Sign up to set email alerts
|

In the Beginning, Escherichia coli Assembled the Proto-ring: An Initial Phase of Division

Abstract: Cell division in Escherichia coli begins by assembling three proteins, FtsZ, FtsA, and ZipA, to form a proto-ring at midcell. These proteins nucleate an assembly of at least 35 components, the divisome. The structuring of FtsZ to form a ring and the processes that effect constriction have been explained by alternative but not mutually exclusive mechanisms. We discuss how FtsA and ZipA provide anchoring of the cytoplasmic FtsZ to the membrane and how a temporal sequence of alternative protein interactions may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 97 publications
(105 reference statements)
1
58
0
3
Order By: Relevance
“…Therefore, FtsZ polymers require at least one membrane-associated factor to tether them to the inner surface of the cytoplasmic membrane. In E. coli , this task is accomplished by a partnership between FtsA and ZipA proteins, which are both essential for cytokinesis and simultaneously associate with the membrane and bind the conserved carboxyl-terminal core peptide of FtsZ 12 . The assembly of these three proteins at the membrane defines the essential part of the proto-ring.…”
Section: Assembly Of the Proto-ringmentioning
confidence: 99%
“…Therefore, FtsZ polymers require at least one membrane-associated factor to tether them to the inner surface of the cytoplasmic membrane. In E. coli , this task is accomplished by a partnership between FtsA and ZipA proteins, which are both essential for cytokinesis and simultaneously associate with the membrane and bind the conserved carboxyl-terminal core peptide of FtsZ 12 . The assembly of these three proteins at the membrane defines the essential part of the proto-ring.…”
Section: Assembly Of the Proto-ringmentioning
confidence: 99%
“…[70][71][72] These proteins associate at the cytoplasmic membrane, forming a scaffold structure into which the other proteins are incorporated. [73][74][75] The attachment to the membrane can also be achieved in vitro by replacing the second player, FtsA or ZipA, by an N-or C-terminal membrane-targeting sequence (mts) added to FtsZ. It is highly conserved in the bacterial domain and the ancestor of eukaryotic tubulin.…”
Section: The Prokaryotic Divisomementioning
confidence: 99%
“…[105] However, it has to be stated that this is only one out of many possible factors that could contribute to the required force. ZipA-FtsZ binding also increases membrane fluidity, [75] while MreB (gray) structures colocalize with Z-ring at mid-cell. Arumugam et al showed that Z-rings contain pre-curved FtsZ filaments, which preferentially orient themselves along curvatures similar to the inner diameter of E. coli cells, but at the same time avoid smaller diameters resembling constriction stages during division.…”
Section: Milestones Of Experimental Researchmentioning
confidence: 99%
“…[64] As mentioned above, FtsZ has multiple spatialr egulators that allow it to coalesce in the form of aZring on the inner membrane at mid-cell (reviewed in Monahan et al [50] ). [66,67] FtsZ polymerization and treadmilling dynamics have been successfully reconstituted on supported lipid bilayersb yu sing FtsZ's native membrane anchors FtsA and ZipA purifiedf rom E. coli. FtsZ cannot bind to the membrane by itself but depends on adaptor proteins such as FtsA and ZipA that recruit FtsZ to the membrane.…”
Section: Ftsz As Ad Ivision Scaffold For Asyncellmentioning
confidence: 99%